Can a populist political party bear the risk of granting complete property rights? Electoral outcomes of Mexico's second land reform - Alain de Janvry; Marco Gonzalez-Navarro; Elisabeth Sadoulet (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The Mexican land reform, one of the most sweeping in the world, proceeded in two steps: it granted peasants highly incomplete property rights on more than half of the Mexican territory starting in 1914, creating strong economic and political dependence for beneficiaries on the ruling political party; and complete property rights starting in 1992, allowing beneficiaries to relate directly to the market. We analyse the impact on political behaviour of switching from incomplete to complete property rights. We use for this the 13-year nationwide rollout of the certification programme and match land reform communities (ejidos) before and after titling with electoral outcomes in corresponding sections across seven electoral episodes. We find that, in accordance with the investor class theory, granting complete property rights induced a conservative shift toward the challenger pro-market party. This shift was strongest where vested interests created larger benefits from market-oriented policies as opposed to public transfer policies. We also find that beneficiaries of the one-time irreversible transfer of a land title failed to reciprocate through votes for the benefactor party, the long time ruling party. The outcome shows that it is difficult for an authoritarian populist party to engage in a land reform that grants complete property rights, suggesting why so many land reforms are either not implemented due to political risk or remain at the ineffective level of incomplete property rights.
Keywords: O13; N66; Q24; P4; 330; land reform; property rights; voting; Mexico; Bodenreform; Eigentumsrecht; Parteipolitik; Mexiko